(3JfhjQ GdCHUGQ aj cjajGJ GdUdGI Ydi GdfHi GdeNJGQ Udi Gddg Ydjg hSde hajeG jMUd dbGQFgG ef GdCLQs - (3YHO Gddg Hf Ydj Hf YHO GdQMef ShjOGf GdOedjLj,J (B1234 (3g` s
(3ChdgG (B:s
(3GdMeO ddg QH GdYGdejf hGdUdGI hGdSdGe Ydi SjOfG eMeO NGJe GdfHjjf hYdi Bdg hUMHg CLeYjf bGd Gddg JYGdi (B:" (3Ef Gddg hedGFcJg jUdhf Ydi GdfHi jG CjgG GdPjf BefhG UdhG Ydjg hSdehG JSdjekG (B" s
(3BNQgG (B:s
(3GdKGdKI hGdCQHYhf PcQgG GdTjHi ai cJGHg eMGSf GdCNHGQ Cf QLdkG Tci GdeQV hhLY GdYjfjf abGd be hJhVC hUd QcYJjf Ke bGd jG ZjGK GdeSJZjKjf abGd be hJhVC hUd QcYJjf Ke bGd jG ZjGK GdeSJZjKjf hUdi Gddg Ydi SjOfG eMeO hYdi Bdg hCUMGHg hGdMes
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B8s
(3GdfSNI HgG MhGTs
(3HChdgG fbhd eNJdaI hahGFOs
(3JUhas
(3HgG fXGe GdJYbjHI s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B107 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B6 - (3U (B89s
Keywords: (3GdeLGejYs